2016
DOI: 10.1002/bem.22023
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of maize seeds exposed to magnetic field

Abstract: Standardization of magnetic field was done for maximum enhancement in germination characteristics of maize seeds. Seeds of maize were exposed to static magnetic fields of strength 50, 100, 150, 200, and 250 for 1, 2, 3, and 4 h for all field strengths. Results indicate that magnetic field application enhanced seed performance in terms of percentage germination, speed of germination, seedling length, and seedling dry weight significantly compared to unexposed control. Among the various combinations of field str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 9 publications
3
29
0
Order By: Relevance
“…HQPM-1) seeds, tomato seeds ( Solanum lycopersicum L. Var. MST/32), and radish ( Raphanus sativus L.) seeds by certain scholars [ 17 , 22 , 37 , 38 , 39 ]. Moreover, studies have also confirmed that the magnetically treated seeds grow higher and heavier than the control, and even increase water uptake [ 22 ].…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…HQPM-1) seeds, tomato seeds ( Solanum lycopersicum L. Var. MST/32), and radish ( Raphanus sativus L.) seeds by certain scholars [ 17 , 22 , 37 , 38 , 39 ]. Moreover, studies have also confirmed that the magnetically treated seeds grow higher and heavier than the control, and even increase water uptake [ 22 ].…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
“…Var: JS-335), corn ( Z. mays L. Var. HQPM-1), and tomato ( L. esculentum ) reported that pretreatment with MF induces greater plant resistance later under water stress conditions, suggesting that this efficiency is related to the improvement of the antioxidant system [ 26 , 37 , 80 ]. Shabrangi and Majd [ 81 ], investigating the effects of drought stress in lentil ( Lens culinaris Medik.)…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
“…Stimulation of plants (including their seeds) with high MF values is described in the literature and carries many other physiological effects (plant reactions in terms of growth, development, photosynthesis, and redox status) [22,30,54,[70][71][72]. Plant seeds were exposed to SMFs, typically from about 5 mT to several hundred mT for different exposure times [45,46,48,51,59,[73][74][75][76][77]. Different intensities of the alternating MF (from several μT to even several hundred mT) for germination of seeds and the growth of seedlings of bean or wheat seeds in various conditions were also examined [32][33][34]37,42,48,[78][79][80][81].…”
Section: Stimulation Of Seeds Germination By the Mfmentioning
confidence: 99%
“…Most scientific papers conclude that the MF has a positive effect on better germination and plant growth, as well as on yield increase [32][33][34][35][36][37][38]. However, these works usually come down to the economic calculation.…”
Section: Introductionmentioning
confidence: 99%